Enhancing students’ writing performance in higher learning through think-write-pair-share: an experimental study / Irwan Affendi Md Naim, Nik Mohd Afiq Nik Luqman and Juan Matmin - Md Naim, Irwan Affendi; Nik Luqman, Nik Mohd Afiq; Matmin, Juan (Universiti Teknologi MARA, 2020)
Think-Write-Pair-Share (TWPS) is a cooperative learning technique which introduced the idea of ‘wait or think’ time, a powerful factor in improving students’ responses to questions. Although the effectiveness of cooperative learning is widely known, few studies have been conducted using TWPS especially at tertiary level ESL writing classrooms. This study investigated the effects of using TWPS on Malaysian tertiary students’ writing performance and investigated their perceptions on the implementation of the technique in their writing lessons. A mixed method design was employed using both quantitative and qualitative data collection approaches. Data was collected from an experimental study (n=80) and semistructured interviews (n=10). After receiving TWPS training, students from the experimental group displayed statistically significant improvement in test scores, and higher than those of the control group. Students’ responses illustrated that cooperative learning enhanced students’ learning experience, individual accountability, motivation as well as improved writing skills. Research findings suggest that TWPS should be considered as a promising technique in improving ESL tertiary students’ performance in writing.